Chronic obstructive pulmonary disease in patients with lung cancer: prevalence, impact and management challenges - Spyratos D (Dove Medical Press, 2017)
Dionisios Spyratos, Eleni Papadaki, Sofia Lampaki, Theodoros Kontakiotis Pulmonary Department, Lung Cancer Oncology Unit, Aristotle University of Thessaloniki, G. Papanicolaou Hospital, Thessaloniki, Greece Abstract: Chronic obstructive pulmonary disease (COPD) and lung cancer share a common etiological factor (cigarette smoking) and usually coexist in everyday clinical practice. The prevalence of COPD among newly diagnosed patients with lung cancer sometimes exceeds 50%. COPD is an independent risk factor (2–4 times higher than non-COPD subjects) for lung cancer development.The presence of emphysema in addition to other factors (e.g., smoking history, age) could be incorporated into risk scores in order to define the most appropriate target group for lung cancer screening using low-dose computed tomography. Clinical management of patients with coexistence of COPD and lung cancer requires a multidisciplinary oncology board that includes a pulmonologist. Detailed evaluation (lung function tests, cardiopulmonary exercise test) and management (inhaled drugs, smoking cessation, pulmonary rehabilitation) of COPD should be taken into account for lung cancer treatment (surgical approach, radiotherapy). Keywords: lung cancer, COPD, coexistence, risk factor, therapy decisions